2009
DOI: 10.1097/bcr.0b013e3181b47cc2
|View full text |Cite
|
Sign up to set email alerts
|

Burn Therapists’ Opinion on the Application and Essential Characteristics of a Burn Scar Outcome Measure

Abstract: Comprehensive burn rehabilitation requires the use of an appropriate burn scar outcome measure (BSOM). The literature reports many BSOMs; however, an objective, practical, inexpensive, valid, reliable, and responsive instrument eludes us. A problem in the development of such a measure is disagreement in which scar properties to include. The objective of this study was to determine the burn scar variables that therapists believe should be included in a BSOM. An Internet survey was administered to burn occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…Hypertrophic scars might be itchy and painful and cause serious functional and cosmetic disability in many burn survivors; almost all burn patients thus complain about the appearance of their scars and suffer from cacesthesia such as itching or pruritus and pain. A previous study reported that the most common and distressful complications of burn patients were abnormal appearance (75.2%), itching (73.3%), and pain (67.6%)14. Itching in the hypertrophic scar continues to be a major obstacle in the rehabilitation of severe burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertrophic scars might be itchy and painful and cause serious functional and cosmetic disability in many burn survivors; almost all burn patients thus complain about the appearance of their scars and suffer from cacesthesia such as itching or pruritus and pain. A previous study reported that the most common and distressful complications of burn patients were abnormal appearance (75.2%), itching (73.3%), and pain (67.6%)14. Itching in the hypertrophic scar continues to be a major obstacle in the rehabilitation of severe burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the most common and distressing complications in burn patients who developed HTSs were abnormal appearance (75.2%), pruritus (73.3%) and pain (67.6%) (45). The cause of pruritus in HTSs and keloid scars is not yet well characterized, but recent studies have indicated the probable involvement of direct activation of opioid receptors identified in the skin (46).…”
Section: Introductionmentioning
confidence: 99%
“…Burn therapists' analysis of burn patient symptomatology revealed that the most common and distressful complications in burn patients were abnormal appearance (75.2%), itch (73.3%) and pain (67.6%) [11]. Itching usually begins at the time of wound closure with maximal intensity at three months often continuing over a year or more with significant impairment of quality of life.…”
Section: Itch/pruritismentioning
confidence: 99%
“…Scar tissue collagen and ECM ground substance is influenced by external vector forces that impact on collagen bundle size and directionality [11,16]. By controlling the biomechanics of the wound environment, new design dressings will have the capacity to improve healing and reduce scar formation [11,15,[17][18][19].…”
Section: Mechanotension and Cell Signalingmentioning
confidence: 99%